Landscape fragmentation and urban sprawl in the urban region of Milan. (4th July 2018) - Canedoli, Claudia; Crocco, Francesco; Comolli, Roberto; Padoa-Schioppa, Emilio
Abstract: Spatial expansion of cities appears to be unavoidable. Despite concern around landscape alterations caused by urban expansion, the understanding of the amounts and patterns of this phenomenon is sorely lacking. In this study, we quantified the current pattern of landscape fragmentation in the urban region (UR) of Milan and analysed the trend of urban sprawl over more than 50 years. The UR of Milan was spatially defined using a standardised and repeatable methodology that combines land-use and population density data. Fragmentation was assessed using the effective mesh size ( m eff ). The trend of sprawl was monitored between 1954 and 2012 and over different areas to detect the magnitude (amount and direction) and patterns of changes. Results revealed a positive trend and a high degree of sprawl over the whole study area.